2013
DOI: 10.1038/ncomms2946
|View full text |Cite|
|
Sign up to set email alerts
|

TRF1 is a stem cell marker and is essential for the generation of induced pluripotent stem cells

Abstract: TRF1 is a component of the shelterin complex that protects chromosome ends. TRF1 deficiency leads to early embryonic lethality and to severe organ atrophy when deleted in adult tissues. Here we generate a reporter mouse carrying a knock-in eGFP-TRF1 fusion allele to study the role of TRF1 in stem cell biology and tissue homeostasis. We find that eGFP-TRF1 expression in mice is maximal in known adult stem cell compartments and show that TRF1 ensures their functionality. eGFP-TRF1 is highly expressed in induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
106
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(120 citation statements)
references
References 51 publications
13
106
1
Order By: Relevance
“…13 Similar findings can be observed in patients with dyskeratosis congenita, a disease characterized by altered telomere maintenance. Dyskeratosis congenita patients show signs of enteropathy and apoptosis because of premature critical shortening of telomeres.…”
Section: Resultssupporting
confidence: 65%
“…13 Similar findings can be observed in patients with dyskeratosis congenita, a disease characterized by altered telomere maintenance. Dyskeratosis congenita patients show signs of enteropathy and apoptosis because of premature critical shortening of telomeres.…”
Section: Resultssupporting
confidence: 65%
“…15 Even so, we previously published a TRF1 ChIP-seq done in induced Pluripotent Stem (iPS) cells, which display high TRF1 levels, showing no significant TRF1 binding to putative regulatory regions nor intragenic binding of this protein outside telomeric regions. 29 Given our negative findings with TRF1, it would be interesting to study the genome-wide DNA binding profiles for TRF2, other shelterin that binds to double-stranded DNA and recruits RAP1 to telomeres. In fact, we previously demonstrated that TRF2 binds to TTAGGG-rich extra-telomeric RAP1 binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will evaluate the effects of TAP68 silencing on cell proliferation as greater cell proliferation was observed with TRF1 lox/lox mice (16). TAP68 suppression may also influence cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TRF1 expression correlates with stem cell pluripotency (16). The functional involvement of TRF1 in mitosis is well established.…”
mentioning
confidence: 99%